Multifunctional Heterogeneous Carbon Nanotube Nanocomposites Assembled by DNA‐Binding Peptide Anchors. Issue 5 (3rd January 2020) - Kim, Kyung‐Il; Yoon, Seokyoung; Chang, Junhyuck; Lee, Seonghyun; Cho, Hui Hun; Jeong, Sun Hwan; Jo, Kyubong; Lee, Jung Heon
Abstract: Although carbon nanotubes (CNTs) are remarkable materials with many exceptional characteristics, their poor chemical functionality limits their potential applications. Herein, a strategy is proposed for functionalizing CNTs, which can be achieved with any functional group (FG) without degrading their intrinsic structure by using a deoxyribonucleic acid (DNA)‐binding peptide (DBP) anchor. By employing a DBP tagged with a certain FG, such as thiol, biotin, and carboxyl acid, it is possible to introduce any FG with a controlled density on DNA‐wrapped CNTs. Additionally, different types of FGs can be introduced on CNTs simultaneously, using DBPs tagged with different FGs. This method can be used to prepare CNT nanocomposites containing different types of nanoparticles (NPs), such as Au NPs, magnetic NPs, and quantum dots. The CNT nanocomposites decorated with these NPs can be used as reusable catalase‐like nanocomposites with exceptional catalytic activities, owing to the synergistic effects of all the components. Additionally, the unique DBP–DNA interaction allows the on‐demand detachment of the NPs attached to the CNT surface; further, it facilitates a CNT chirality‐specific NP attachment and separation using the sequence‐specific programmable characteristics of oligonucleotides. The proposed method provides a novel chemistry platform for constructing new functional CNTs suitable for diverse applications. Abstract : This work reports a simple and generalizable method to introduce diverse functional groups on carbon nanotube (CNT) surfaces and construct heterogeneous CNT nanocomposites using deoxyribonucleic acid (DNA) binding peptide anchors. Using this strategy, any desired functional group of choice, such as thiol, biotin, and carboxylic acid, can be easily introduced on CNT surfaces with controlled density and ratio.